The Influence of Artificial Intelligence (AI) and Mobile Learning on Learning Outcomes in Higher Education: Did the Mediation of Self-Competence Matter? - Priamono, Gilang Hardiansyah; Hakim, Arif Rahman; Daryono, Rihab Wit (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
Islamic Religious Education (PAI) has a significant impact on the development of students' character, morality, and overall learning outcomes. This study aims to investigate the effects of artificial intelligence (AI) and mobile learning on student learning outcomes, with a specific focus on the role of students' self-competence as a mediating factor. Employing a quantitative survey approach, the research included 208 students from the PAI Study Program at IAIN Ponorogo, using probability sampling techniques. Data was collected through Likert-scale questionnaires, and the research data was analyzed using PLS-SEM analysis. The results indicate a positive influence of AI and mobile learning on student learning outcomes, with self-competence playing a crucial role as a mediating factor. These findings highlight the importance of educators promoting self-regulation, self-efficacy, and motivation skills within online learning environments. The study emphasizes the potential of integrating AI and mobile learning to enhance the quality of education and recommends that educators continuously update their knowledge of technological advancements through training and collaboration. Strengthening these competencies can lead to a more interactive, personalized, and adaptive learning environment for students.